ANALISIS PUISI BERJUDUL “AKU INGIN” KARYA SAPARDI DJOKO DAMONO MENGGUNAKAN TEORI ABRAMS (KAJIAN PRAGMATIK) - Ratnaningsih, Dewi; Hayati, Dwi (Jurnal Buana Kata: Pendidikan, Bahasa, dan Ilmu Komunikasi, 2024)
In this analysis, the literary works studied are literary works in the form of poetry. Poetry is a literary work that contains expressions of the author’s heart in which there is a rhythm, lyrics, rhyme and rhythm in each line. Poerty presented in imaginative language and composed with coherent and meaningful words, poerty itself contains an aesthetic value. This poem will be studied using a pragmatic study which actually comes from the study of abrams literary criticism which focuses on the funcation of literature. Approach or study is one way of appreciating a work, an approach or study related to how and from where we perceive a work. Whereas according to (Gunawan: 1994) pragmatics is a study of the relationship between language and its contect.   Pada analisis kali ini karya sastra yang dikaji ialah karya sastra berupa puisi. Puisi merupakan sebuah karya sastra yang berisi ungkapan isi hati penulis dimana didalamnya terdapat suatu irama, lirik, rima, dan ritme di setiap barisnya. Puisi disajikan dengan bahasa yang imajinatif serta disusun dengan kata yang padu dan bermakna, puisi sendiri mengandung suatu nilai estetika. Puisi ini akan dikaji menggunakan pendekatan pragmatik yang sesungguhnya berasal dari pendekatan kritik sastra abrams yang berfokus pada fungsi sastra. Pendekatan ialah salah satu jalan dalam mengapresiasi suatu karya, pendekatan yang berkaitan dengan bagaimanaserta dari mana kita memandang suatu karya. Sedangkan menurut (Gunawan:1994) pragmatik merupakan suatu kajian mengenai hubungan antara bahasa dengan konteksnya.